Temperatism. Volume 1, A new way to think about business and doing good - Foster, Carrie (New York, New York : Business Expert Press, 2018)
This book isn't intended to have all the answers, but explores the question 'How much wealth is enough?' Examining the idea that the capitalist profit agenda is not benefiting society or democracy, Temperatism investigates whether there is an alternative to the profit agenda currently followed by organizations and society. If growth and profit are an important part of the equation, then the question that arises is "Important for what purpose?" What follows is a proposition of an alternative agenda of doing good and the introduction of a new business framework--temperatism.
1. Introduction -- 2. Why now? Why temperatism? -- 3. Where are we now? -- 4. Introducing a different agenda, temperatism -- 5. Doing good and what that means -- 6. More than capitalism with a heart -- 7. Property and employment -- 8. Attempting to achieve economic democracy -- 9. Good citizenship is good business -- 10. People and purpose before profit -- 11. The chequered history of CSR -- 12. The place of organizations in society -- 13. Conclusions -- References -- Index.
Includes bibliographical references and index.
Description based on print version record.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2018. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Common good; Business and politics; Industries -- Social aspects; Social responsibility of business; Legacy; Electronic books